Análise geotécnica de suscetibilidade aplicada ao estudo de caso dos paredões de janeiro no parque nacional de Ubajara – Ce - Carnielli, Álan Liupekevicius (2022)
Located in the region between the Western Peripheral Depression of Ceará and the Serra de Ibiapaba, on the eastern edge of the Parnaíba Basin, there is an area of study for this work, known as the Paredões de Janeiro region (PJ). This area is allocated in the domains of the Conservation Unit (UC) of the Ubajara National Park (PNU), in its annexed area, located in the municipality of Tianguá - CE. The PNU has relevant flows as geotouristic attractions in the state of Ceará and this receives an elevator of visitors annually. This touristic context adjusted to the geomorphological context, characterized by an abrupt and erect relief on the cornice of the Serra de Ibiapaba. This situation is an alert for the high potential of risks related to the processes of landslides and recovery of rocky slopes in the region. This is due to the main attractions and visiting geological sites linked to geological structures defined through the process of nudation and retreat of the structure of the Serra. From this problem and historical events, related to accidents in Conservation Units and National Parks, the project work of a geological/structural and geotechnical analysis in the Paredons de Janeiro. The Mirante da Pedra do Espia stands out in the region, which is the main place to visit and with its viewing platform on a block imminent of rupture. The Mirante da Racha da Rosa and the Mirante da Gameleira, the Corredor do Índio, Olho da Cobra, Cachoeira Véu da Noiva and Grande Canyon canyons were analyzed. In field campaigns, the rock mass and natural slopes were characterized, simultaneously with the systematic survey of rock structures and continuities. From this information, from aerial photogrammetry to qualitative methodologies of geomechanical classification such as; RQD (Rock Quality Designation Index), RMR (Rock Mass Rating), and GSI (Geological Strength Index), presenting results ranging from poor to fair and occasionally good. Rocsience package software was used for geotechnical modeling and assessment. Our Serra Grande formation, which is specific to a study area and laboratory layer, has been installed for technological characterization. Structurally - close as; F1 family with Nthe 75°W/85°SW, associated with the decompression of the massif and the formation of the canyons and viewpoints of the Paredes de Janeiro. Family F2A and F2B, orthogonal in front of the escarpment and with altitudes respectively of N20°E/90°NE and N20°E/90°NE. mainly slopes of the blocks and failure planes and failure fall with express blocks of failure type mainly. of large blocks of rock disconnected from the massif and tilted with the forward rotation of the escarpment of the mountain, indicating a process of overturning blocks.